Short postsurgical antibiotic therapy for spinal infections: protocol of prospective, randomized, unblinded, noninferiority trials (SASI trials) - Betz, Michael; Uçkay, Ilker; Schüpbach, Regula; Gröber, Tanja; Botter, Sander M.; Burkhard, Jan; Holy, Dominique; Achermann, Yvonne; Farshad, Mazda (Trials, 2020)
Abstract Background There are several open scientific questions regarding the optimal antibiotic treatment of spinal infections (SIs) with or without an implant. The duration of postsurgical antibiotic therapy is debated. Methods We will perform two unblinded randomized controlled trials (RCTs). We hypothesize that shorter durations of systemic antibiotic therapy after surgery for SI are noninferior (10% margin, 80% power, α = 5%) to existing (long) treatment durations. The RCTs allocate the participants to two arms of 2 × 59 episodes each: 3 vs. 6 weeks of targeted postsurgical systemic antibiotic therapy for implant-free SIs or 6 vs. 12 weeks for implant-related SIs. This equals a total of 236 adult SI episodes (randomization scheme 1:1) with a minimal follow-up of 12 months. All participants receive concomitant multidisciplinary surgical, re-educational, internist, and infectious disease care. We will perform three interim analyses that are evaluated, in a blinded analysis, by an independent study data monitoring committee. Besides the primary outcome of remission, we will also assess adverse events of antibiotic therapy, changes of the patient’s nutritional status, the influence of immune suppression, total costs, functional scores, and the timely evolution of the (surgical) wounds. We define infection as the presence of local signs of inflammation (pus, wound discharge, calor, and rubor) together with microbiological evidence of the same pathogen(s) in at least two intraoperative samples, and we define remission as the absence of clinical, laboratory, and/or radiological evidence of (former or new) infection. Discussion Provided that there is adequate surgical debridement, both RCTs will potentially enable prescription of less antibiotics during the therapy of SI, with potentially less adverse events and reduced overall costs. Trial registration ClinicalTrials.gov , NCT04048304. Registered on 5 August 2019. Protocol version 2, 5 July 2019.